2021
DOI: 10.1021/acscatal.1c00783
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Pd(II)-Catalyzed E/Z Isomerization of Unactivated Alkenes: Evidence for a Monometallic Nucleopalladation Pathway

Abstract: Pd(II)-catalyzed E/Z isomerization of alkenes is a common process-yet is largely uncharacterized, particularly with non-conjugated alkenes. In this work, the mechanism of Pd(II)-catalyzed E/Z isomerization of unactivated olefins containing an aminoquinoline-based amide directing group is probed using in situ kinetic analysis, spectroscopic studies, kinetic modeling, and DFT calculations. The directing group allows for stabilization and monitoring of previously undetectable intermediates. Collectively, the data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…To establish whether or not isomerization or C–H bond activation occurs on the alkenyl amine substrates, we carried out the reaction using deuterated trifluoroacetic acid in the absence of an aryl iodide coupling partner (Scheme a). After performing the reaction, we found that no alkene isomerization had occurred with the free amine as a directing group . Meanwhile, the trans -starting material was partially deuterated at the γ-position, while the cis -starting material was not.…”
Section: Methodology and Resultsmentioning
confidence: 97%
“…To establish whether or not isomerization or C–H bond activation occurs on the alkenyl amine substrates, we carried out the reaction using deuterated trifluoroacetic acid in the absence of an aryl iodide coupling partner (Scheme a). After performing the reaction, we found that no alkene isomerization had occurred with the free amine as a directing group . Meanwhile, the trans -starting material was partially deuterated at the γ-position, while the cis -starting material was not.…”
Section: Methodology and Resultsmentioning
confidence: 97%
“…[63] In contrast, 1,2-disubstituted internal alkenes exhibit low reactivity and provide a mixture of regio-and stereoisomers because the Mizoroki-Heck reaction with internal olefins produces a mixture of (E) and (Z)-products even from a single geometrical isomer. [64] Alternatively, allylic functionalization can proceed through a π-allyl palladium complex via a Tsuji-Trost type reaction, which has also been widely explored. In this mechanism, an electrophilic π-allyl palladium complex reacts with a nucleophile to form an allylic product at the same time as a zerovalent catalyst.…”
Section: Pd-catalyzed Dehydrogenative Coupling Mechanismmentioning
confidence: 99%
“…Specifically, alkenes bearing electron withdrawing groups tend to provide trans β ‐substituted alkenes whereas alkenes with electron donating groups generate α ‐substituted alkenes [63] . In contrast, 1,2‐disubstituted internal alkenes exhibit low reactivity and provide a mixture of regio‐ and stereoisomers because the Mizoroki‐Heck reaction with internal olefins produces a mixture of ( E ) and ( Z )‐products even from a single geometrical isomer [64] …”
Section: General Reaction Mechanism For Aerobic Oxidative Couplingmentioning
confidence: 99%
“…At the time we could not determine conditions to achieve the selective monoarylation reaction of the terminal allylamines, which as mentioned would give rise to the important class of cinnamylamines. In addition, while we had a good handle on the competing mechanisms for the arylation of cinnamylamines to form the 3,3-diarylallylamines, we lacked a similar understanding of how the first arylation occurred – did it also come from a competition between C–H activation (followed by possible isomerization) 15 and γ-selective Mizoroki–Heck coupling, or could the terminal alkene be directly arylated without the involvement of the amine, which under acidic conditions would be protonated. 16 The goal of this work was therefore to determine conditions that would allow us to access cinnamylamines directly, and to address some of the outstanding questions regarding the mechanism of the first arylation.…”
Section: Introductionmentioning
confidence: 99%